2009
DOI: 10.1111/j.1365-246x.2009.04214.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake swarms on transform faults

Abstract: S U M M A R YSwarm-like earthquake sequences are commonly observed in a diverse range of geological settings including volcanic and geothermal regions as well as along transform plate boundaries. They typically lack a clear mainshock, cover an unusually large spatial area relative to their total seismic moment release, and fail to decay in time according to standard aftershock scaling laws. Swarms often result from a clear driving phenomenon, such as a magma intrusion, but most lack the necessary geophysical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
167
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(186 citation statements)
references
References 51 publications
16
167
0
3
Order By: Relevance
“…The associated pressure pulses are suggested to trigger aftershocks by reducing the effective normal stress of incipient slip at Bibliothek des Wissenschaftsparks Albert Einstein on September 29, 2016 http://gji.oxfordjournals.org/ Downloaded from applies. However, aftershock migration related to fluid-driven processes was reported to be significantly smaller (<1 km s −1 ) (Roland & McGuire 2009, and references therein) than the observed migration velocity flowing the first day after the Illapel 2015 earthquake. A further test of the viability of these or other ideas will require indepth modelling, for example, of diffusion processes and Coulomb stress changes, beyond the scope of this study.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…The associated pressure pulses are suggested to trigger aftershocks by reducing the effective normal stress of incipient slip at Bibliothek des Wissenschaftsparks Albert Einstein on September 29, 2016 http://gji.oxfordjournals.org/ Downloaded from applies. However, aftershock migration related to fluid-driven processes was reported to be significantly smaller (<1 km s −1 ) (Roland & McGuire 2009, and references therein) than the observed migration velocity flowing the first day after the Illapel 2015 earthquake. A further test of the viability of these or other ideas will require indepth modelling, for example, of diffusion processes and Coulomb stress changes, beyond the scope of this study.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…Blakely et al (2011) suggested that the Wooded Island earthquakes and aseismic slip were caused by flexing of shallow strata associated with movement on underlying, larger structures that form the concealed Yakima Ridge. Notably the geodetic moment of the inferred deformation sources was significantly larger (eight times) than the cumulative seismic moment of the swarm, a feature observed in swarms elsewhere (Roland and McGuire, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…We assumed a faulting volume of 1:5 km × 0:75 km × 0:2 km and used an elasticity constant of 30 GPa to determine an effective seismic stress drop of 0.6 MPa. Although this value should not be compared to the stress drop of individual events, it is close to the median values obtained by Roland and McGuire (2009) and Chen et al (2012) for other swarms, such as the Brawley, Obsidian Buttes, and Salton trough sequences in the Imperial Valley of southern California. Creep events have been shown to have similar effective stress drops (Brodsky and Mori, 2007).…”
Section: State Of Stress and Effective Stress Dropmentioning
confidence: 97%
“…The simplest clusters are mainshock-aftershock sequences that exhibit rapid increase in moment release, follow Båth's law (Richter, 1958) with the mainshock magnitude ∼1:5 units larger than the largest aftershock, have high-effective stress drop, and exhibit a temporal decay following the Omori law (Omori, 1907). In contrast, swarm sequences exhibit a gradual increase of moment release, deviate from Båth's law, have low effective stress drop, and, in some cases, exhibit slow Omori-like temporal decay (Roland and McGuire, 2009). The occurrence of swarms is usually explained with two different mechanisms, pressure front stress increase associated with fluid flow or aseismic creep on a slip surface, which both facilitate cascading failures of nearby asperities (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation